Temporal trend of the dropout rate and vaccination coverage of the triple viral vaccine in Brazil, 2014-2021 - Lívia de Lima Moura; Mercedes Neto; Reinaldo Souza-Santos (Ministério da Saúde do Brasil, 2023)
Abstract Objective: to analyze the temporal trend of coverage and dropout rate for triple viral vaccine in Brazil, according to the country's Federative Units and Macro-Regions, between 2014 and 2021. Methods: this was an ecological time series study, using data from the National Immunization Program Information System and the Live Birth Information System; joinpoint regression models were used. Results: in Brazil as a whole annual vaccination coverage was below 95% and ranged from 92.3% (2015) to 54.4% (2021); the second dose of the vaccine showed a decreasing temporal trend in the period (average change over the period = -5.8; 95%CI -10.5;-0.8); the temporal trends were stationary and decreasing in the country's Federative Units; the dropout rate ranged from 22.2% (2014) to 37.4% (2021). Conclusion: there was a downward trend in vaccination coverage and an increase in the dropout rate in Brazil as a whole and in the country's Federative Units.